Implementasi Hukum Humaniter dan Perlindungan Warga Sipil dalam Konflik Israel-Palestina - Beruh, Sri Marantika; Martiono, Frisdian; Susilo, Tarsisius; Haryana, Syaid; Supriyanto, Agus (Syntax Corporation, 2025)
The ongoing armed conflict between Israel and Palestine reflects the complexity of modern geopolitical contestation, characterized not only by military confrontation but also by widespread violations of fundamental principles of International Humanitarian Law (IHL). This study aims to analyze the gap between the normative framework of humanitarian law as outlined in the 1949 Geneva Conventions and their Additional Protocols and the empirical practices observed on the battlefield, particularly concerning the protection of civilians and non-military infrastructure. Employing a juridical-normative method and a technocratic-institutional approach, this research examines the legal and institutional dimensions that hinder the effective enforcement of IHL. The findings reveal that, in addition to the low level of state actor compliance with the principles of distinction, proportionality, and precaution, the weakened role of the United Nations Security Council and the limited jurisdictional reach of the International Criminal Court exacerbate the culture of impunity for war crimes. Based on these findings, the study recommends a structural reform of international institutions, including the reconfiguration of supranational legal authority independent of political vetoes, and the strengthening of a collaborative, adaptive legal framework for civilian protection. This study aspires to offer a strategic contribution toward reinforcing international legal governance in responding to increasingly asymmetric and destructive contemporary armed conflicts.